Penerapan Model Quantum Teaching untuk Meningkatkan Hasil Belajar Siswa Kelas IV Sekolah Dasar - Dewi, Rahmi Citra; Desyandri, Desyandri; Miaz, Yalvema (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
This study aims to describe the application of the Quantum Teaching model to improve student learning outcomes in social studies learning. This research is a classroom action research that uses qualitative and quantitative approaches. The subjects of this study were 28 teachers and fourth grade students. The implementation of this research was carried out in two cycles with research procedures consisting of planning, implementation, observation and reflection. The results of research was improve a) RPP cycle I 83.9% and cycle II 92.8%. b) Implementation of teacher aspects and aspects of students cycle I 80.5% and cycle II 94.4%, c) Student learning outcomes cycle I 78.5 and cycle II 87. Thus, the application of the Quantum Teaching model can improve learning outcomes students in social studies learning in Grade IV SD Negeri 08 Pisang Kota Padang